Direct live imaging of cell–cell protein transfer by transient outer membrane fusion in Myxococcus xanthus - Adrien Ducret; Betty Fleuchot; Ptissam Bergam; Tâm Mignot (eLife, 2013)
In bacteria, multicellular behaviors are regulated by cell–cell signaling through the exchange of both diffusible and contact-dependent signals. In a multicellular context, Myxococcus cells can share outer membrane (OM) materials by an unknown mechanism involving the traAB genes and gliding motility. Using live imaging, we show for the first time that transient contacts between two cells are sufficient to transfer OM materials, proteins and lipids, at high efficiency. Transfer was associated with the formation of dynamic OM tubes, strongly suggesting that transfer results from the local fusion of the OMs of two transferring cells. Last, large amounts of OM materials were released in slime trails deposited by gliding cells. Since cells tend to follow trails laid by other cells, slime-driven OM material exchange may be an important stigmergic regulation of Myxococcus social behaviors.